The relationship between shoulder disorders and instrument group in professional Australian orchestral musicians. (7th October 2012) - Jacklyn, G; Driscoll, T; Ackermann, B
Abstract : Background: Professional musicians have high rates of musculoskeletal disorders, but few studies have analysed the risk of shoulder pain and injury by instrument group and work environment. Aims/Objectives/Purpose: To assess the prevalence and impact of shoulder pain and injury, and its relation to instrument group, in professional musicians from Australian orchestras. Methods: 374 musicians from six professional Australian orchestras completed a physical examination and cross-sectional questionnaire concerning their demographics, duties and physical activities at work. The outcome variable, left and right shoulder pain and injury, was assessed using a subjective pain score—the visual analogue scale—and objective physical examination. Prevalence rates were estimated and associations with risk factors assessed by logistic regression. Results/Outcomes: Shoulder pain and injury is common amongst professional orchestral musicians. The overall estimate for right and left shoulder pain was 19% and 12% respectively. There was an association between right shoulder injury and instrument group. Woodwind (OR 2.22 95%; CI 0.99 to 5.00) and upper string musicians (OR 2.28; 95% CI 1.02 to 5.09) had a significantly higher OR when compared to brass players. Significance/Contribution to the Field: The findings reinforce the fact that shoulder disorders are common amongst professional orchestral musicians and highlight the need for prospective research into the occupational exposures that contribute to this problem.